Petroleum hydrocarbon-contaminated soil bioremediation assisted by isolated bacterial consortium and sophorolipid. (15th March 2021) - Feng, Leiyu; Jiang, Xiupeng; Huang, Yanning; Wen, Dongdong; Fu, Tianyu; Fu, Rongbing
Abstract: Pollution in soil by petroleum hydrocarbon has become a global environmental problem. The bioremediation of petroleum hydrocarbon-contaminated soil was enhanced with the combination of an isolated indigenous bacterial consortium and biosurfactant. The biodegradation efficiency of total petroleum hydrocarbon (TPH) was increased from 12.2% in the contaminated soil to 44.5% and 57.7% in isolated consortium and isolated consortium & 1.5 g sophorolipid (SL)/kg dry soil, respectively. The half-life of TPH degradation process was decreased from 32.5 d in the isolated consortium reactor to 20.4 d in the isolated consortium & 1.5 g SL/kg dry soil. The addition of biosurfactant into contaminated soils improved the TPH desorption from solid matrix to the aqueous solution and the subsequent solubilization, which ultimately improved the bioavailability of TPH in contaminated soils. Biosurfactant also served as carbon sources which contributed to the stimulation of cell growth and microbial activity and accelerated the biodegradation process via co-metabolism. The enzyme activities and quantities of functional genes were demonstrated to be incremented in SL reactors. The biosurfactant improved the TPH bioavailability, stimulated the microbial activities and participated in the co-metabolism. The combination of bioaugmentation and SL benefitted the bioremediation of petroleum hydrocarbon-contaminated soil. Graphical abstract: Image 1 Highlights: Bioremediation of TPH-contaminated soil was enhanced by isolated consortium and SL. Bioavailability of TPH in contaminated soils was improved in the presence SL. SL served as carbon sources to stimulate of cell growth. Activities of key enzymes and functional genes in biosystems were enhanced by SL. SL accelerated the biodegradation of TPH via co-metabolism. Abstract : Capsule: Bioremediation of petroleum hydrocarbon-contaminated soil was facilitated efficiently by isolated indigenous bacterial consortium and sophorolipid.